(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article is devoted to the problems of organizing auditing activities in Uzbekistan on the basis of Information Technology and the areas of their elimination, the article includes the types of software used in international audit practice, factors affecting the non-application of software related to auditing in the audit process, problems of applying modern software in audit processes, the procedure for forming an auditor’s opinion, in the audit, the possibilities achieved by the use of Information Technology are described on the basis of the author’s opinions.